Parachuting psychoactive substances: Pharmacokinetic clues for harm reduction. (March 2018) - Daveluy, Amélie; Géniaux, Hélène; Baumevieille, Marie; Létinier, Louis; Matta, Marie-Noëlle; Lazès-Charmetant, Aurélie; Haramburu, Françoise; Guéroult, Pascale
Abstract: Background: Parachuting, also called bombing, is a way to ingest psychoactive substances wrapped into cigarette paper, toilet paper, etc. There is little data describing parachuting in terms of substances use, context of use and, most importantly, the motivations for using such wrappers, although some authors hypothesized that parachute could be used for pharmacokinetic reason. However, inconsistently, some authors report that parachutes are used for sustained-release whereas others report that users are looking for an immediate effect. Research design and methods: Considering parachute as a "home-made" dosage form, we have applied the dissolution testing to characterize the dissolution performance of a substance wrapped into a parachute and to characterize whether a parachute represents an immediate-release form or not. Results: This in-vitro study provides the first pharmacokinetic data for drugs wrapped in parachutes. It shows that parachute acts as sustained-release form when made with a cigarette paper wrapper, but as immediate release form in the presence of alcohol or if wrapped with toilet paper. Conclusions: An important message to harm reduction is that users must be aware that a parachute can have unexpected pharmacokinetics and have to avoid taking another parachute in the absence of an immediate-effect to avoid overdose. Highlights: Parachuting is a way to ingest psychoactive substances wrapped into cigarette paper. Parachute acts as sustained-release form when made with a cigarette paper wrapper. Parachute acts as immediate release form in the presence of alcohol. This is a message for harm reduction to avoid overdose. Users must avoid taking another parachute in the absence of an immediate-effect.